The Consequences of War in (The Curse of Newbaharan) from the Perspective of Ecofeminism Criticism - Yasin Braim Qadir; Pakhshan Sabir Hamad (Zanco Journal of Human Sciences, 2026)
This paper is entitled The Consequences of War in (The Curse of Newbaharan) from the Perspective of Ecofeminism Criticism. After the modernism period, particularly in the 1970s, literary criticism developed significantly in the world, along with various theories, methods and new movements emerged as well. Ecocriticism, including ecofeminism, draws on insights from both environmental critics and feminists. This study likely focuses on environmentalism and the negative and destructive consequences of war on the environment, nature and humans, more specifically on women. Additionally, in this study, the concepts, terms and definitions of war, environment, environmental criticism, and ecofeminism have been examined from numerous viewpoints. Importantly to us, is knowing how Kurdish novelists have perceived the dangers of war to environment and particularly how feminist-environmental is reflected in their texts. This study can be promoting environmental awareness and fostering responsibility among individuals in preventing the destruction of nature and ecosystem’s environment. Since, human survival is related to the health of environment, particularly the quality of earth, water and air. Simultaneously, respecting and preserving these elements is crucial for a beautiful, healthy and sustainable environment which directly leads to reducing its threats as well.